2020
DOI: 10.3389/fnins.2020.574499
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Signaling in Vascular Function and Stroke

Abstract: The oxytocin receptor (OXTR) is a G protein-coupled receptor with a diverse repertoire of intracellular signaling pathways, which are activated in response to binding oxytocin (OXT) and a similar nonapeptide, vasopressin. This review summarizes the cell and molecular biology of the OXTR and its downstream signaling cascades, particularly focusing on the vasoactive functions of OXTR signaling in humans and animal models, as well as the clinical applications of OXTR targeting cerebrovascular accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 265 publications
(395 reference statements)
0
15
0
1
Order By: Relevance
“…As OT has pleiotropic effects, the therapeutic perspectives are truly exciting. Indeed, OT has broad implications for general health: OT is a stress-coping molecule with anti-inflammatory and antioxidant properties; influences the immune system, body composition, cognitive functions and mood; and has been tested in the treatment of numerous diseases, including anxiety, pain, diabetes, cardiovascular diseases and breast cancer [1,27,[40][41][42][43][44][45].…”
Section: Oxytocin As a Therapeutic Agent: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…As OT has pleiotropic effects, the therapeutic perspectives are truly exciting. Indeed, OT has broad implications for general health: OT is a stress-coping molecule with anti-inflammatory and antioxidant properties; influences the immune system, body composition, cognitive functions and mood; and has been tested in the treatment of numerous diseases, including anxiety, pain, diabetes, cardiovascular diseases and breast cancer [1,27,[40][41][42][43][44][45].…”
Section: Oxytocin As a Therapeutic Agent: Perspectivesmentioning
confidence: 99%
“…OT is recognized to play a role in social behavior and stress coping, is involved in the regulation of hippocampal plasticity and memory formation, and increases the functional activity and connectivity in frontal regions associated with the impairment in autism [41,58]. It has been reported that the OT receptors' polymorphisms are associated with impaired memory in humans, and OT knockout in mice displays memory deficit [43]. A systematic review of the effects of OT treatment in frontotemporal dementia reports an improvement in cognition and behavioral symptoms with a good tolerance [58].…”
Section: Oxytocin As a Therapeutic Agent: Perspectivesmentioning
confidence: 99%
“…The cardiovascular system is one of oxytocin’s important targets [ 2 , 3 ]. Oxytocin and its receptors are expressed in the heart and its vascular cells [ 4 ]. In the cultured brain microvascular endothelial cells (BMEC), oxytocin inhibits ox-LDL-induced monocyte adhesion to BMEC and the expression of adhesion molecules [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic administration of oxytocin reduces atherosclerotic plaque and inflammation in the aorta of ApoE -/- mouse [ 6 ]. It has been proposed that the intrinsic oxytocin system may play a critical role in the maintenance of cardiovascular homeostasis [ 2 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin was first discovered in 1906 for its uterine-contracting properties [ 1 ] and shortly after, its involvement in lactation was described [ 2 , 3 ]. Since the beginning of the 20th century, numerous studies have revealed the involvement of oxytocin in a range of biological functions, including cell growth and regulation, wound healing, and anti-inflammatory actions as well as social behaviors such as mother–infant attachment and pair-bonding [ 4 , 5 , 6 , 7 , 8 ]. Along this line of research, compelling evidence has accumulated, establishing the role of oxytocin in appetite regulation, eating behavior, weight status, and metabolism in both animal models and humans [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%